Conventional markers in determination of activity of sarcoidosis - Gungor, Sinem; Ozseker, Ferhan; Yalcinsoy, Murat; Akkaya, Esen; Can, Günay; Eroglu, Hacer; Genc, Nilgün Sema (International immunopharmacology, 2015)
Currently, there are no objective criteria to determine sarcoidosis activity. The present study aimed to discover a sensitive serum marker that would determine the activity of sarcoidosis and can be used during disease follow-up. Forty-eight patients with sarcoidosis and twenty healthy volunteers as a control group were included in the study. On their control visits, the patients were divided into active and inactive groups based on their clinical, physiological, and radiological status. Angiotensin converting enzyme (ACE), adenosine deaminase (ADA), total IgE (T-IgE), C-reactive protein (CRP), serum amyloid-A (SAA), and soluble interleukin-2 receptor (sIL2R) serum levels and classical findings of activity were compared, and the utilization of these parameters as markers of activity was investigated. Thirty-nine cases were female (female/male: 39/9) and the mean age was 44.29±10.9years. Thirty-seven cases were active and 11 cases were inactive. Serum ACE, ADA, sIL2R, and SAA levels were significantly higher while T-IgE levels were lower in the sarcoidosis cases. A comparison of the markers between active and inactive cases showed that only SAA was significantly higher (p<0.001). sIL2R was elevated in cases with extra-pulmonary involvement (p<0.014). The area under the curve value was rather high for ADA (0.98 CI: 0.96–1.0); it also had high sensitivity (93.8%) and specificity (100%), and therefore had the highest diagnostic value (96.6%). The current study showed that SAA wil be helpfull for detecting the activity of srcoidosis, IL2R measurement in exploring the extra-pulmonary organ involvement. •Clinical activity criteria were used to determine the activity, and than serum amyloid-A,(SAA), C reactive protein(CRP), angiotensin converting enzyme (ACE), adenosine deaminase(ADA), soluble interleukin 2R(sIL2R), and total IgE levels analyzed to separate the variety of active and inactive cases.•Except for the CRP, all of the serum markers were different between normal cases and sarcoidosis patients.•In the active cases, SAA is higher than the other serum markers.•We reported that if sarcoidosis is suspected, SAA level is used for both the diagnosis and determination of the activity of sarcoidosis.